Recrystallization upon solvent vapor annealing and impact of polymer crystallinity on hole transport in poly(3-hexylthiophene):small molecule blends. Issue 8 (2nd September 2020) - Chlebosz, Dorota; Janus, Krzysztof; Danielewicz, Kinga; Goldeman, Waldemar; Czapik, Agnieszka; Glaßer, Gunnar; Mezger, Markus; Kiersnowski, Adam
Abstract : This work demonstrates an impact of molecular architecture of aromatic diimides on crystal morphology and hole mobility in their blends with P3HT. The effect of solvent-vapor annealing on recrystallization of the blends is discussed in detail. Abstract : This work is a systematic study on charge carrier (hole) mobility and structure of binary blends of poly(3-hexylthiophene) (P3HT) with small-molecular aromatic diimides (ADIs): N, N ′-di( n -hexyl)benzene-1, 2, 4, 5-tetracarboxylic diimide, N, N ′-di( n -butyl)- or N, N ′-di( n -hexyl)naphthalene-1, 4, 5, 8-tetracarboxylic diimide. The blends were spray coated to form films and kinetically stabilized by solvent vapor annealing that caused their recrystallization. The hole mobility determined in organic field-effect transistors based on the blends was found to correlate with the molecular architecture of ADIs (their alkyl-to-aromatic ratios). Generally, the alkyl-dominated ADIs enhanced or were inert, whereas the aromatic-dominated ADIs worsened the hole mobility measured in the blends directly after the spray coating. Grazing-incidence X-ray diffraction studies supported by electron microscopy indicated that the solvent vapor annealing caused the ADI crystals to grow, but reduced (typically by 35%) P3HT crystal sizes, and caused their reorientation from 'face-on' to 'edge-on'. ADIs enhanced the crystallinity degree of P3HT in some blends, even up to as high as ∼0.9. Flipping the orientation, reducing the sizes of P3HT crystals and increasing P3HT crystallinity degree in the blends all together contributed to ∼2- to ∼7-fold improvements in hole mobility. ADIs' molecular architecture exerted a sound influence on orientation and sizes of P3HT crystal domains. Reduction in P3HT crystal sizes and increasing the number of P3HT crystal domains exerted a stronger influence on hole mobility increase than the face-on to edge-on reorientation.